2017
DOI: 10.1017/s0025315417001801
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variations in life-history traits and statolith trace elements of Sepioteuthis lessoniana populations around northern Taiwan

Abstract: The bigfin reef squid Sepioteuthis lessoniana is a neritic species widely distributed in coastal waters of the Indo-Pacific region and is of interest to fisheries for its high commercial value. Squid samples were collected from Keelung (KL) and Penghu (PH), around northern Taiwan from October 2012 to September 2013. A total of 949 squid were examined, and 620 squid were aged using statoliths. The age range of the squid in KL (55–183 days) was similar to that in PH (77–186 days). The squid hatched almost year-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…According to statolith δ 18 O values, most probably the individuals of the spring and summer groups hatched near the coasts of northeastern Taiwan, with an occurrence probability of 1; these findings support empirical evidence that the waters near the coast of northeastern Taiwan are one of main spawning grounds for S. lessoniana (Chen et al, 2015;Ching et al, 2017). The dominant topography in northern Taiwan is that of an eroded coastline with complicated topographical features and structures (Song et al, 1997), forming macroalgae-rich and coral-rich environments for spawning.…”
Section: Prediction Of Ontogenetic Movement and Geographical Distribusupporting
confidence: 79%
See 2 more Smart Citations
“…According to statolith δ 18 O values, most probably the individuals of the spring and summer groups hatched near the coasts of northeastern Taiwan, with an occurrence probability of 1; these findings support empirical evidence that the waters near the coast of northeastern Taiwan are one of main spawning grounds for S. lessoniana (Chen et al, 2015;Ching et al, 2017). The dominant topography in northern Taiwan is that of an eroded coastline with complicated topographical features and structures (Song et al, 1997), forming macroalgae-rich and coral-rich environments for spawning.…”
Section: Prediction Of Ontogenetic Movement and Geographical Distribusupporting
confidence: 79%
“…In general, loliginid squids spawn throughout the year and consequently exhibit multicohort formation along with highly diverse dispersion patterns; hence, high levels of genetic diversity are achieved in the populations of these cephalopods (O'dor, 1998). A study reported that the elemental signatures in the entire statolith exhibited less variation between S. lessoniana samples from northern Taiwan and the Penghu Islands for the same season (Ching et al, 2017). This finding suggests a high level of population connectivity in S. lessoniana in Taiwan.…”
Section: Prediction Of Ontogenetic Movement and Geographical Distribumentioning
confidence: 98%
See 1 more Smart Citation
“…Considerable exibility in squid life-history traits (LHTs) has been assumed to be one of the pivotal factors contributing to the increase of squid stocks worldwide, which appears to be a result of the ability of squids to adapt successfully to environmental changes (Pecl et al, 2004;Pecl and Jackson, 2005;Hoving et al, 2013;Doubleday et al, 2016). There is great variability in LHTs in a wide range of squid species (Pierce et al, 2005;Ichii et al, 2009;Ching et al, 2019), which is considered to be a mixture of intrinsic variability and the in uence of environmental factors, especially water temperature and food availability (Vidal et al, 2002;Pecl and Jackson, 2005;Pierce et al, 2008;Yu et al, 2015). Signi cant differences in growth and size-at-maturity have been observed in different geographical and seasonal cohorts for various squid species (Arkhipkin et al, 2000;Jackson and Moltschaniwskyj, 2002;Jackson et al, 2003;Ceriola and Jackson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the original publication of this article (Ching et al, 2017) the author order and affiliations were mistakenly presented. They should appear as below:…”
mentioning
confidence: 99%